2019
DOI: 10.1101/746875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disome-seq reveals widespread ribosome collisions that recruit co-translational chaperones

Abstract: Regulation of translation elongation plays a crucial role in determining absolute protein levels and ensuring the correct localization and folding of proteins. Much of our knowledge regarding translation elongation comes from the sequencing of mRNA fragments protected by single ribosomes (ribo-seq). However, larger protected mRNA fragments have been observed, suggesting the existence of an alternative and previously hidden layer of regulation. In this study, we performed disome-seq to sequence mRNA fragments p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 66 publications
(69 reference statements)
2
18
0
Order By: Relevance
“…showing that short polybasic sequences promote ribosome collisions and are enriched in the ribosome exit tunnel of the disomes [29]. The authors argue that the translation of these disomes is likely to resume without recruiting the RQC pathway and, they hypothesize that these polybasic-induced pauses (and collisions) can favor the co-translational folding of upstream sequences [29]. Recently, the yeast gene SDD1 was identified as a natural target of RQC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…showing that short polybasic sequences promote ribosome collisions and are enriched in the ribosome exit tunnel of the disomes [29]. The authors argue that the translation of these disomes is likely to resume without recruiting the RQC pathway and, they hypothesize that these polybasic-induced pauses (and collisions) can favor the co-translational folding of upstream sequences [29]. Recently, the yeast gene SDD1 was identified as a natural target of RQC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that ribosomes with open A sites produce shorter mRNA fragments (20-22 nucleotides) than ribosomes with occupied A sites, which produce the longer mRNA fragments (27)(28)(29) nucleotides) analyzed in Figure 3a [35]. Structural and biochemical evidence demonstrated that the electrostatic repulsion caused by the presence of a polybasic sequence inside the exit tunnel can decrease the binding efficiency of an incoming tRNA carrying an additional positively charged residue, leading to empty A site ribosome [25,39,68].…”
Section: Ribosome Profiling Of Endogenous Proteins With Polybasic Seqmentioning
confidence: 99%
See 3 more Smart Citations